DISTRIBUSI SPASIO -TEMPORAL NITROGEN DI DAERAH TANGKAPAN AIR DANAU TONDANO PROVINSI SULAWESI UTARA - Wantasen, Sofia; Luntungan, Joudie N. (Bumi Lestari; Vol 16 No 1 (2016), 2016)
The spatio temporal distribution of nitrogen in catchment area of   Lake Tondano wasimportant to investigate because agricultural residue comes from the catchment potentiallydecreased water quality in Lake Tondano. The purpose of this study was to examine thedistribution of nitrogen spatially and temporally in the catchment area of Lake Tondano.The study was conducted in the field and laboratory. Water quality sampling conducted byusing composite sampling on the rivers, lake Tondano and outlet of irrigation channels.The data collected was the total nitrogen, nitrate, ammonia in 2001, 2008 and 2014. Datawere analyzed using Graph Method and Spatial Analysis.        The results showed that the distribution of total nitrogen that has a high concentrationfound in the outlet streams and irrigation canals outlet. High nitrate accumulates in theoutlet of Lake Tondano. Nitrate concentration can be divided into 9 (nine) classes, namelyconcentration of 0.100 to 0.211 mg / l; 0.211 to 0.322 mg / l;  0.322 to 0.433 mg / l;  0.433 to0.544 mg / l; From 0.544 to 0.655 mg / l; From 0.655 to 0.766 mg / l; 0.766 to 0.877 mg / l;0.877 to 0.988 mg / l; and 0,988- 1,100 mg / l. Ammonia, spatially spread evenly on thesurface of Lake Tondano. Ammonia concentration can be divided into 9 (nine) class is aclass that has a concentration of 0.000 to 0.064 mg / l; From 0.064 to 0.129 mg / l; 0.129 to0.193 mg / l; From 0.193 to 0.258 mg / l; 0.258 to 0.322 mg / l; 0.322 to 0.387 mg / l; From0.387 to 0.451 mg / l; 0.451 to 0.516 mg / l; and from 0.516 to 0.580 mg / l. Concentrationsof nitrate and ammonia fluctuated from year to year of observation. This was influenced byfertilization in rice fields.
Keywords: Spatio temporal distribution, nitrogen, Catchment area of Lake Tondano